ARspace: Augmented Reality and Visual Analytics for Improving and Monitoring the Quality of Public Space - Case: Las Nieves Neighborhood in Bogota, Colombia - Daniel Salamanca Díaz; José Tiberio Hernández (Interaction Design and Architecture(s), 2019)
Public space is a prerequisite for sustainable living, and it should be planned with the citizens´ needs as a starting point. In this paper, the process to carry out a collaborative environment is explained in order to support the improvement of the quality of public space through direct participatory processes. After analyzing previous works, a different approach was explored: generation of data and information based on people’s proposals and ideas and not on reports or complaints about the current state of public space. Augmented reality was chosen as a way for creating proposals and visual analytics in order to support collaboration and decision-making processes. Results showed a high level of acceptance by the stakeholders and, despite the difficulty in district institutions to work collaboratively and involve citizens, they acknowledged it is necessary to have comprehensive and inclusive visions to manage public space.